Secretion of Cell Wall Polymers into the Growth Medium of Lysis-Defective Pneumococci During Treatment with Penicillin and Other Inhibitors of Cell Wall Synthesis - Waks, Susan (1978)
Autolysin-defective pneumococci secrete into the growth medium choline-containing macromolecules during treatment with any one of a large number of inhibitors of cell wall biosynthesis, including beta-lactams, beta-halogeno-d-alanines, cephalosporins, and d-cycloserine. Secretion is closely related to the dose response of the bacteria to the various drugs: (i) secretion can already be detected at the minimum inhibitory concentration; (ii) the rate and extent of secretion is dependent upon the drug concentration; and (iii) secretion commences within minutes after the addition of the antibiotics to the cultures. Reversal of the growth-inhibitory effect of benzylpenicillin (by penicillinase addition) is accompanied by a halt in secretion just at the time when the bacteria resume normal growth. Secretion of the choline-containing macromolecules seems to be a specific consequence of the inhibition of peptidoglycan biosynthesis, since inhibition of growth by drugs affecting protein, ribonucleic acid, or deoxyribonucleic acid synthesis does not cause secretion. The choline-containing macromolecules include both the pneumococcal lipid-containing teichoic acid (Forssman antigen) and wall teichoic acids made after the addition of antibiotics. The appearance of these macromolecules in the growth medium is not due to the hydrolytic activity of an autolysin, since penicillin-induced secretion could be demonstrated in autolysin-defective mutants, in pneumococci grown on ethanolamine-containing medium (such cells are known to have defective autolytic systems), and in wildtype pneumococci grown under conditions nonpermissive for lysis.